Opportunities for Colombia under the pacific alliance-Singapore Free Trade Agreement (2022)
On Wednesday, January 26, 2022, in the Colombian city of Buenanetura, the Pacific Alliance Member States (Chile, Colombia, Mexico and Peru) signed a free trade agreement with the Republic of Singapore. According to the Ministry of Trade and Industry of Singapore (n.d.), this deal, negotiations for which began in September 2017, covers five main areas: trade in goods, trade in services and investment, government procurement opportunities, e-commerce, and international maritime transport services.